Modification of varicose vein stripping to achieve immediate compression in a theatre setting with minimum personnel - Francis, Joseph; Nazer, Nihaz Y. (International Surgery Journal, 2020)
Compression bandaging is a key aspect following stripping for varicose vein surgery. With adequate compression, formation of subcutaneous hematoma can be prevented and thereby prevent revascularisation of the hematoma leading to recurrence of varicose vein. Various techniques exist to provide compression. Our modification provides an easy alternative to achieve immediate compression following stripping and is especially useful in a setting where staff is very limited. Materials required include a 10 cm width gauze bandage, 1% lidocaine with epinephrine, and number 1 silk suture in addition to the conventional tools for open varicose vein surgery. The gauze bandage is introduced along with the stripper which is passed from groin to below knee. The bandage is kept in the subcutaneous tunnel till perforator ligation, groin wound closure and application of compression bandage. The gauze bandage is removed through a small window within the compression stocking below the knee and the wound closed in a single layer. From 2005 to 2020, 410 patients underwent varicose vein surgery with the modified technique. Of these, 1 patient developed complication secondary to hematoma formation which was managed conservatively. Our modification of the varicose vein stripping technique is shown to be a cost effective and simple technique which provides immediate compression and effortlessly facilitates haemostasis till wounds are closed and compression stockings applied. in various literatures.